Evaluasi Pemasaran Berbasis 4P terhadap Kepuasan Konsumen dengan SEM-PLS (Structural Equation Modelling-Part Least Square) - Jufriyanto, Moh.; Muslimah, Tsaqofi Bintang; Setiawan, Agus (Universitas Suryakancana, 2024)
Ikhtiar MSMEs are MSMEs engaged in the production and sale of taro chips. The existence of similar MSMEs selling chips makes the competition even tighter. Consumer behavior has also changed, due to the variety of types of chips available and by consumer wishes. In addition, Ikhtiar MSMEs want to know the characteristics of consumers to provide good product output, so that consumers feel satisfied with the product. From these problems, Ikhtiar MSMEs implement marketing strategies. The strategy used is through four variables, namely product, price, promotion, and location. Each variable has sub-variables. From the results of the implementation, Ikhtiar MSMEs want to know the factors that affect consumer satisfaction. The method used is SEM-PLS (Structural Equation Modelling-Part Least Square). The SEM-PLS method not only explains the presence or absence of relationships between latent variables (prediction) but SEM-PLS can also be used to confirm the theory. From the results of the study, based on the evaluation of the measurement model, the research model was declared valid and reliable. From the evaluation of the structural model, the research model of the implementation of the MSME marketing strategy Ikhtiar towards consumer satisfaction is declared feasible and valid. The level of customer satisfaction from the implementation results was 89.2%. Variables that contribute to consumer satisfaction are products and promotions.